Factors Affecting The Development Of Al-Maidah Pemalang Umkm - Imti Ramadhanti, Liga; Sutrisno,; P, Ratih Hesty Utami (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to analyze the influence of product innovation, brand image and promotion on purchasing decisions through customer satisfaction. This research was conducted at UMKM Al-Maidah Pemalang. The research method uses quantitative research using a sample of 105 respondents. The technique used in data collection uses a questionnaire as a data collection instrument. Data processing techniques use the SmartPLS3 application. The results of this research are that product innovation has no effect on customer satisfaction. Meanwhile, brand image and promotion influence customer satisfaction. Product innovation has no effect on purchasing decisions through customer satisfaction. Meanwhile, brand image and promotion influence purchasing decisions through customer satisfaction.